2010
DOI: 10.1021/jp107323p
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Hydrogen Adsorption in Metal−Organic Frameworks by Mg2+ Functionalization: A Multiscale Computational Study

Abstract: By means of multiscale theoretical techniques, we examined the ability of Mg 2+ to enhance H 2 storage in metal-organic frameworks. Ab initio calculations showed that Mg 2+ increases more than five times the interaction energy between the hydrogen molecules and the new proposed organic linker of the IRMOF-10, reaching the value of 4.73 kcal/mol. The substituted group of the linker may host up to five hydrogen molecules with an average interaction energy of 3.1 kcal/mol per H 2 molecule. GCMC atomistic simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…However, so far there is no binding energy results available in literature to validate our calculations except for unmodified linker, benzene dicarboxalate mentioned above. Our investigation is in agreement with previous studies that showed modification of MOFs models increases the interaction energies between hydrogen molecule and MOFs[11,25,[37][38][39][40][41] . From the investigations it can be concluded that using density functional theory based on PW91/DN level (GGA functional) and M06-2X methods is reliable for accurate H 2 binding energies on the models of modified linkers.Table3.…”
supporting
confidence: 93%
“…However, so far there is no binding energy results available in literature to validate our calculations except for unmodified linker, benzene dicarboxalate mentioned above. Our investigation is in agreement with previous studies that showed modification of MOFs models increases the interaction energies between hydrogen molecule and MOFs[11,25,[37][38][39][40][41] . From the investigations it can be concluded that using density functional theory based on PW91/DN level (GGA functional) and M06-2X methods is reliable for accurate H 2 binding energies on the models of modified linkers.Table3.…”
supporting
confidence: 93%
“…In general, hydrogen can be stored in different forms [5]. The possible approaches to store hydrogen are physical storage of compressed hydrogen gas in high pressure tanks (up to 700 bar), physical storage of cryogenic hydrogen (cooled to -253°C, at pressures of 6-350 bar in insulated tanks) and the storage in the solid matrix [6][7][8][9][10]. Among these methods, the cheapest and safest storage is the adsorption of hydrogen in special solids.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we deduced that Fe III /ZSM-5 zeolite may not be suitable for hydrogen storage because the adsorbed H 2 molecules are facile to decompose but difficult to restore [12,19]. Some other metal ions within zeolites, e.g., Mg II [9,16,25], were suggested as good candidates for hydrogen storage. Areán et al [9,10,[25][26][27][28][29] characterized the thermodynamics of H 2 adsorption in metal-exchanged zeolites and metal-organic frameworks (MOF), and observed a positive correlation between the enthalpy and entropy changes (DH 0 and DS 0 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some other metal ions within zeolites, e.g., Mg II [9,16,25], were suggested as good candidates for hydrogen storage. Areán et al [9,10,[25][26][27][28][29] characterized the thermodynamics of H 2 adsorption in metal-exchanged zeolites and metal-organic frameworks (MOF), and observed a positive correlation between the enthalpy and entropy changes (DH 0 and DS 0 ). To the best of our knowledge, most of the computational works were related with the adsorption of a single H 2 molecule, and only a few with two H 2 molecules [10,22].…”
Section: Introductionmentioning
confidence: 99%